High-power lithium-ion capacitor using orthorhombic Nb(2)O(5)nanotubes enabled by cellulose-based electrospun scaffolds - Park, Jong Chel; Park, Sangbaek; Kim, Dong-Wan (SPRINGER, 2020)
Orthorhombic Nb2O5-based nanoarchitectures have shown promise as electrode materials for Li-ion capacitors because they improve lithium ion transport and conductivity of Nb(2)O(5)with high theoretical capacity. However, despite the several advantages of nanotubes, the facile synthesis of Nb(2)O(5)nanotubes remains challenging. Herein, we present Nb(2)O(5)nanotubes as an efficient ion- and electron-conducting electrode using environmentally friendly cellulose as sacrificial templates. The rational synthetic design based on sol-gel interactions with hydroxyl groups on the cellulosic surface enables uniformly covering the electrospun-cellulose one-dimensional templates with Nb2O5, resulting in unusual nanotubular Nb(2)O(5)crystals featuring crystallographic iso-orientation owing to a controlled two-step calcination. Such crystallographically oriented nanotubes are favorable to fast Li(+)intercalation kinetics for pseudocapacitive behavior with efficient lithium ion channels. The orthorhombic Nb(2)O(5)nanotubes provide electrodes with a high initial capacity (163 mAh g(-1)), excellent rate capability (95 mAh g(-1)at 5 A g(-1)), and stable cycle performance (81.8% retention after 1000 cycles at 5 A g(-1)) without any carbon composite and are thus superior to previously reported Nb(2)O(5)electrodes. This simple strategy can open a new avenue for fabricating nanotubes of various transition metal oxides. Graphic abstract
Keywords: METAL-OXIDE FILMS; NB2O5 NANOBELTS; CARBON; NANOFIBERS; TIO2; CRYSTALLINITY; TRANSITION; STORAGE; SUPERCAPACITOR; NANOSTRUCTURE